Incidence, severity, prognostic significance of thrombocytopenia in malaria - Rao, Bezwada Srinivasa; Vani, Matta Sree; Latha, Gurindapalli Jyothi Swarna Laya; Lavanya, Dondapati (International Journal of Research in Medical Sciences, 2017)
Background: Malaria is an infectious disease caused by plasmodium parasite. P. falciparum account for majority of morbidity and mortality. Thrombocytopenia and anaemia are the most frequently associated hematological complications in malaria. The low platelet count together with acute febrile syndrome emerged as the strongest predictor of malaria a finding that is frequent and present even before anemia and splenomegaly sets in. Severe thrombocytopenia is a good predictor of poor prognosis than mild and moderate thrombocytopenia. The aim is to study the incidence, severity, prognostic significance of thrombocytopenia in malaria. Methods: This was an observational and prospective study. The study enrolled 100 patients with thrombocytopenia and fever who were proven to have malaria either by peripheral smear or Quantitative Buffy Coat (QBC) test or malarial antigen assay were included in the study and patients with thrombocytopenia due to other causes were excluded from the study. Platelet count was estimated on a fully automated quantitative analyzer. All the 100 patients were followed during the hospital stay and upto discharge or till the outcome. Results: The incidence of thrombocytopenia was 73% indicating a common association in malaria. Complicated malaria was observed in 58.80% of P. falciparum infection whereas 66% of P. vivax infection was associated with uncomplicated malaria. Severe thrombocytopenia showed positive correlation with severity of malaria. Thrombocytopenic patients with effective anti-malarial treatment showed 95.90% recovery and 3 patients 4.10% had mortality. Patients with severe thrombocytopenia were 8.5 times more likely to have complicated malaria with P <0.001 according to student ‘t’ test. Conclusion: Thrombocytopenia is the most common hematological finding in malaria. Severe thrombocytopenia showed positive correlation with complicated malaria and a good predictor of poor prognosis. Patients with classical malarial fever and thrombocytopenia who were negative for malaria parasite were not included in the study.